Complex anisotropic fracture behaviors of 3D-printed fiber-reinforced composites based on multi-scale hierarchical microstructure. (8th February 2022) - Yu, Siwon; Bale, Hrishikesh; Park, Seunggyu; Hwang, Jun Yeon; Hong, Soon Hyung
Abstract: 3D printing allows large flexibility to control the alignment of fiber orientations engineered to the closely matched design requirements, making it advantageous for manufacturing fiber-reinforced composites with customized characteristics. Quantitative three-dimensional observation of inherent fracture behavior of 3D-printed composites has so far been a challenge due to its printing direction dependence. This article aims to clarify the structural hierarchy and anisotropic fracture behaviors of 3D-printed fiber-reinforced composites. We prepared two unidirectional and two alternate layup composite specimens for comparison and explored the resultant microstructures and fracture behaviors. In-situ X-ray tomography provided successive 3D images of fracture initiation and propagation at each tensile load increment to clearly define the progressive fracture mechanisms. The color-coded segmentation images described in detail the crack growth process during the uniaxial tension and highlighted the different fracture modes between specimens. The 3D-printed composites showed the complex anisotropic fracture behaviors based on the multi-scale hierarchical microstructure where the intermediate filaments embedded with micron-size reinforcing fibers form a macro-scale integrated single matrix. The complex fracture process occurred simultaneously at the micro-scale fiber-matrix interface as well as the macro-scale inter-filament interface. Eventually, 3D-printed composites reached the final failure following various fracture mechanisms represented by localized deformation, interfacial failure, heterogeneous cracking behavior, and structural evolution according to the localized orientation of printed materials to the tensile loading direction. Our effort will be the first step in finding the origins of the structural hierarchy and anisotropic fracture behaviors of 3D-printed fiber-reinforced composites. Graphical abstract: Image 1